The adoption of Web Assurance Services (WAS) among Malaysian online retailers - Shahifol Arbi, Ismail; Ahmad, Halimah @ Nasibah; Hassan, Nor Laili (Universiti Utara Malaysia, 2004)
Trust is one of important elements for e-commerce (EC) success. This study investigates the adoption of Web Assurance Services (WAS) by Malaysian online retailers, which could increase the online trust in e-commerce activities. By using popular Internet search engines, 85 online retailers were sampled. Frequency tests, Chi-square and Kruskal-Walis tests were employed to test the data. The results of this study show that most Malaysian online retailers do not adopt WAS. The retailers’ web site models significantly differ between the retailers who adopt WAS and who do not adopt WAS. On the other hand, their business types and customers-bases were not significantly different. This study is important in shedding some light of the awareness of the importance of online trust among Malaysian online retailers. This study also gives auditing firms and other organizations in Malaysia some information on the opportunity of offering WAS.